ФОЛКНЕР—ВЕЛИКИЙ ДЕЯТЕЛЬ АМЕРИКАНСКОЙ ЛИТЕРАТУРЫ (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article deals with the life and works of the famous American writer William Faulkner. As a modernist, he experimented with forms and styles to create a new literature that reflected the loss of reality inherent in modernism. Furhtermore this article is about Faulkner's works, which are mostly novels and short stories, and it was noticed that in all his works he incorporated the scenery of the world of Yoknapatawpha that imaginary created county which was put into the plot as a separate space in his works.